Changing Ecological Conditions in the Marine Environment Generate Different Microbial Food Web Structures in a Repeatable Manner - Šolić, Mladen; Šantić, Danijela; Šestanović, Stefanija; Kušpilić, Grozdan; Matić, Frano; Vrdoljak Tomaš, Ana; Jozić, Slaven; Bojanić, Natalia; Ninčević Gladan, Živana (Frontiers in Marine Science, 2022)
The mechanisms responsible for the development of various structural and functional features of the microbial food web (MFW) and their dynamics at spatial and temporal scales, which are important for predicting their responses to future environmental changes, are largely unknown. More than 3000 datasets of environmental and microbial variables collected over a decade on a seasonal and large spatial scale in the Adriatic Sea were analyzed. The sets of environmental variables were classified into four clusters (representing different environmental states) using Neural Gas analysis and the differences in MFW structure between the clusters were analyzed. Different variants of MFW evolve in the different clusters in terms of the abundance of MFW components, their ratios, growth and grazing rates, predator preference in prey selection, the strength of predator-prey interaction, and the relative importance of top-down and bottom-up control. However, these clusters are neither spatially nor temporally fixed; rather, the area studied represents a mosaic of different environmental conditions that alternate from one state to another on a time scale. In each of the environmental states, a distinct structure of MFW develops that shows consistent and repeatable changes that strictly follow the switching in environmental conditions from one state to another.